A male preponderance in patients with Indian post kala‐azar dermal leishmaniasis is associated with increased circulating levels of testosterone. (4th November 2015) - Mukhopadhyay, Debanjan; Mukherjee, Shibabrata; Ghosh, Susmita; Roy, Susmita; Saha, Bibhuti; Das, Nilay Kanti; Chatterjee, Mitali
Abstract: Background: Post kala‐azar dermal leishmaniasis (PKDL) is a neglected parasitic disease that occurs after apparent cure from visceral leishmaniasis (VL) and poses a challenge for elimination of VL, being its proposed reservoir. Several epidemiological studies have proposed that sex hormones may account for the increased susceptibility of males towards infectious diseases, including leishmaniasis; however, the role of testosterone and sex bias, if any, in PKDL has not been evaluated. Methods: The study population included 87 patients with PKDL and 39 with VL; levels of testosterone were measured by competitive enzyme‐linked immunosorbent assay along with their levels of antileishmanial immunoglobulin and IgG. The association of testosterone, if any, was then correlated with age, gender, humoral response, lesional profile, disease duration, and lag period. Results: A male predominance was evident in PKDL, not in VL; importantly, this male bias was predominant postpubertal, strongly indicative of an association between sex hormone and disease progression. Male patients with PKDL had significantly higher levels of testosterone, which regressed significantly with miltefosine, not with sodium antimony gluconate. Additionally, a significant correlation was found between plasma testosterone and antileishmanial IgG. Conclusion: Taken together, our study has established a male dominance in PKDL, which showed a strong association with testosterone. This information should be taken into consideration for disease monitoring and control.